Marx: crítica à dimensão política - Paixão, Bruno Gonçalves da (2016)
This thesis analyzes the essentiality that permeates the politics dimension of Marx. Understanding essence as predominant features of a way of being or category try to demonstrate here that the politics, in all the Marxian works, has a negative character. This interpretive filter assumes, not a purely conceptual analysis of the category alluded above, as ethereal form, but his connection with the materiality of life, that is to say as part of a historical development of social relations of production. In this sense, the alleged discussion will seek the DNA of the Politics in the emergence of private property as a necessary element of mediation of the class struggle that begins with such sociability. The politics comes as social power usurped as a dimension that appears to regulate the relations of domination of one class over the other, always acting for the deactivation of the social, thus having an essentially negative character. This Marxian finding breaks with the perspective of the philosophical tradition where the policy appears as an intrinsic dimension to be social, and therefore, the development of the latter would be coupled to the first, that is all output to humanity's problems could only be solved in the framework and improving the policy. For Marx, on the contrary, improved policy is to prolong any sociability built on the pillars of social classes, keeping intact the exploitation of man by man. The solution to overcoming such relational status between men, according to Marx, it is the political revolution of social soul, thus opposing to any previous revolutionary attempt that for the German thinker, they were social revolutions of political soul. Beyond the simple exchange of words in position, the concept of revolution is central to the Marxian work it points to overcome the political emancipated society.